Subcritical nucleation process for producing stable atomic clusters of subcritical size and the structure, properties and applications of materials made from these clusters
By controlling the rapid expansion and cooling conditions of the vapor cloud, the problem of the destruction of the subcritical size clusters during the condensation process is solved, and the manufacturing and application of stable subcritical size clusters is achieved.
Patent Information
- Application Number
- CN202080017190.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-02-27
- Filing Date
- 2020-02-27
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2040-02-27
AI Technical Summary
The prior art is difficult to manufacture and stabilize atomic clusters of subcritical sizes, resulting in the failure of these clusters to form industrially useful materials during the condensation process.
By controlling the rapid expansion and cooling conditions of the vapor cloud, it is ensured that multiple subcritical size clusters formed during the subcritical nucleation process are condensed and remain stable.
Stable subcritical size clusters, including sub-nano-sized carbon clusters, have been successfully manufactured, and these clusters can be used to form materials with special properties, suitable for a variety of applications.
Smart Images

Figure CN113574012B_ABST
Abstract
Description
Technical Field
[0001] The field of the invention relates to subcritical nucleation processes for producing stable atomic clusters of subcritical size, and the structure, properties and applications of materials made from these clusters. For carbon, this means clusters formed from subcritical-sized nuclei, the size of which is less than 1 nm, and the nucleation process occurs under temperature and pressure conditions where the critical size of carbon is 1 nm.
[0002] Portions of the disclosure of this patent document contain material which is subject to copyright protection. The copyright owner has no objection to the facsimile reproduction by anyone of the patent document or the patent disclosure, as it appears in the Patent and Trademark Office patent file or records, but otherwise reserves all copyright rights whatsoever. Background Art
[0003] Nanotechnology, defined as the manipulation of matter with at least one dimension ranging from 1nm to 100nm in size, has been the subject of intensive research and commercial interest in recent years. Matter has special and unusual properties in this field, and a host of new materials and devices are being created using nanotechnology. Nanomedicine, nanoelectronics, nanomaterials are just some of the diverse application areas.
[0004] The use of laser ablation to create carbon nanotubes has been known for many years; a block of graphite is placed in an oven, a laser is pointed at it, and argon is pumped in the direction of the laser spot. The oven temperature is about 1200°C. As the laser ablates the target, a carbon plasma is formed, which then condenses; during the condensation, multiple atomic clusters are formed, each arranged into a carbon nanotube, and carried by the gas flow to a cold copper current collector. See Guo T, Nikolaev P, Rinzler D, Tomanek DT, Colbert DT, Smalley RE (1995). "Self-Assembly of Tubular Fullerenes". J. Phys Chem 99(27): 10694–7.
[0005] Fullerenes such as C60 and C70 can also be obtained by using laser ablation [H. Kroto et al., Nature 318, 162-163 (1985)]. However, fullerenes and nanotubes, as stable allotropic forms of carbon, require a relatively long time under quasi-equilibrium conditions for their formation. This is fundamentally different from the formation of subcritical size nanoclusters, where non-equilibrium conditions and short formation time are crucial.
[0006] However, it is believed that it is possible to grow stable carbon clusters in a cooling carbon vapor cloud when the nuclei (a) have a supercritical size (e.g., a size greater than 1 nm) or (b) are intrinsically stable like C60. On the other hand, subcritical nuclei that are intrinsically unstable (i.e., return the carbon atoms to the gas phase almost instantly) have received little attention. Therefore, the possibility of preserving these subcritical nuclei in some way so that they can be collected and formed into industrially useful materials has not been considered. 'Subcritical nucleation' occurs at the initial stage of the phase transition from the plasma gas phase to the solid phase; this is when intrinsically unstable nuclei smaller than the critical size begin to form in the plasma; because these subcritical nuclei are highly unstable, it is conventionally understood that they will become stable and thus form useful materials only when and if they reach and exceed the critical size. It is noted that the term 'critical size' refers to the cluster size at which the minimum energy required to generate the atomic cluster reaches a maximum; therefore, the 'subcritical size' is a size smaller than the 'critical size'. For carbon, this is 1 nm under certain pressure and temperature conditions. The atom can be carbon, or another substance, such as silicon (whose critical size is generally close to that of carbon).
[0007] Analysis of the vapor condensation literature suggests that it is believed that after the initial phase, the expansion and cooling of the gas vapor results in the complete and total destruction of any and all subcritical-sized nuclei or clusters formed from the subcritical nucleation process. Therefore, nuclei or clusters formed from subcritical nucleation processes are believed to be so unstable that useful, stable, subcritical-sized clusters cannot be made in any production process.
[0008] This instability is explained as follows: Generally speaking, subcritical size atomic clusters that appear in the hot and dense vapor cloud during the initial stages of vapor condensation are highly unstable, rapidly appearing and disappearing as atoms exchange with the vapor phase. The possibility of generating stable subcritical size clusters (e.g., subnanometer or sub-1 nm size clusters where the atoms are carbon atoms) by changing the vapor conditions so that subcritical nuclei that would normally be completely destroyed are retained and thus can be collected and used has been ignored in favor of intensive and continued research and development in the field of nanotechnology, i.e., supercritical size carbon clusters (e.g., carbon size greater than 1 nm).
[0009] The present invention overturns the long-held view that stable subcritical size clusters, i.e., clusters of atoms smaller than the relevant subcritical size and formed by a subcritical nucleation process, cannot be produced by changing the vapor conditions, so that subcritical nuclei that would normally be completely destroyed are retained.
[0010] This specification describes a fabrication process for generating stable subcritical size clusters, although they are generated during a subcritical nucleation process; a theoretical model explaining the formation conditions of these stable subcritical size clusters; and the structure, properties and application range of these subcritical size clusters. Summary of the invention
[0011] The present invention is a process for making stable atomic clusters of subcritical size, wherein a vapor cloud undergoes rapid expansion and rapid cooling, wherein vapor conditions or parameters are controlled so that a plurality of stable clusters each of which is smaller than the critical size formed during subcritical nucleation are condensed. The process essentially changes the vapor conditions or parameters so that subcritical nuclei that would normally be completely destroyed are retained. These clusters are then formed into materials having useful properties. Further details are in the appended claims section.
[0012] Terminology Note:
[0013] "Subcritical cluster" refers (whether capitalized or not) to a cluster or group of single atoms formed by a subcritical nucleation process, which is, for example, a process that would normally result in the complete destruction of the cluster. The cluster is thus a solid form of a subcritical nucleus that can be considered to be in the gas phase. Once cooled and formed into a useful material, the size of the cluster will generally remain below the critical size for that particular element, although it may also exceed it. Thus, for carbon we are dealing with clusters that are typically in the range of 0.3 or 0.4 nm to 0.7 nm individually. Clusters in useful materials are typically in this size range, but they can also exceed it, for example reaching a size of 1.5 nm.
[0014] "Subnano cluster" means (whether or not capitalized) a cluster or group of individual atoms of a subcritical size less than 1 nm formed by a subcritical nucleation process, e.g., a process that would normally result in the complete destruction of the cluster. Since the critical size of carbon in a plasma vapor cloud is 1 nm (although it varies depending on the precise temperature and pressure conditions in the plasma vapor cloud), carbon subcritical clusters will generally also be subnano clusters since, as noted above, they will generally fall within the size range of 0.3 or 0.4 nm to 0.7 nm.
[0015] "Nanocluster" refers (whether capitalized or not) to a cluster or group of single atoms formed by a subcritical nucleation process, such as a process that would normally result in the complete destruction of the cluster, wherein the size of the cluster may be less than 1 nm or greater than 1 nm; nanocluster may also refer to clusters of subcritical size, as well as clusters of supercritical size. Thus, a 'nanocluster' material is a material made of clusters, each of which may be completely subcritical in size, or partially subcritical and partially supercritical in size, or completely supercritical in size. Thus, a carbon 'nanocluster' material is a material made of carbon clusters, each of which may be completely subcritical in size, or partially subcritical and partially supercritical in size, or completely supercritical in size. For the materials we have studied, the carbon clusters are primarily in the size range of 0.3 or 0.4 nm to 0.7 nm, but, as mentioned above, there may be some clusters that fall outside this range, such as 1.5 nm in size. We may refer to carbon-based nanoclusters as "nanocarbons" or "nC".
[0016] We use the word "structure" (whether capitalized or not) primarily in the context of the arrangement of atoms that forms a single cluster, such as a sub-1 nm carbon cluster. As we will describe later in this specification, for stable carbon subnanoclusters, molecular dynamics modeling suggests that one possible structure is a disordered, amorphous arrangement of 64 carbon atoms. Individual clusters are likely to have significantly different numbers of carbon atoms (significantly fewer than 64, or more). However, we can exclude the well-known C60 fullerene allotrope from our reference to a disordered, amorphous subcritical cluster because (a) it is not a disordered, amorphous structure, and (b) it is not understood to be formed by a subcritical nucleation process that would normally result in the complete destruction of the cluster.
[0017] We use the term "material" (whether capitalized or not) to refer to the situation where there are many of these clusters together. Thus, in the fabrication method we will describe, a powder or film is made up of tens of thousands of these subcritical clusters; we call it a 'material'.
[0018] We use the term 'stable' in its generic sense, i.e. unlikely to change under the conditions of its normal use. More strictly, one could say 'metastable' - i.e. stable except under extreme conditions such as heat or pressure, and we will use the term 'stable' in this sense.
[0019] In general, we will use the term "nanocluster" in a general sense to refer to groups or clusters of atoms that may be above or below a subcritical size. A "nanocluster material" is a material composed of multiple clusters of atoms; some or all of these clusters may each be below the critical size; some or all of them may be above the critical size. Thus, for a "carbon nanocluster material", the stable clusters of atoms that make up the material may each be below the 1 nm critical size, or larger, or a mixture of the two. A "subnanocluster material" is composed of clusters of stable atoms, each of which is primarily, or (in the extreme case) all, below the critical size. In the case where the atoms are carbon, the critical size is 1 nm, so we refer to the special case of a "carbon subnanocluster material", which is composed of stable clusters of carbon atoms, each of which is primarily, or (in the extreme case) all, below the 1 nm critical size. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1a is an STM image of a carbon material deposited as a thin film on a substrate.
[0021] FIG1b is a surface profile obtained by STM along the green line shown in FIG1a.
[0022] FIG. 1c is an STM image of a single carbon cluster of a carbon material located on the smooth surface of highly ordered pyrolytic graphite.
[0023] Figure 1d is a surface profile obtained by STM along the green line shown in Figure 1c. The size of the cluster is 0.4 nm.
[0024] Figure 2 This is an image of a carbon cluster consisting of 64 carbon atoms simulated by molecular dynamics. The cluster structure is disordered (amorphous).
[0025] Figure 3 is the Raman spectrum of carbon material. The spectrum shape corresponds to amorphous carbon material.
[0026] Figure 4 It is the nitrogen adsorption-desorption isotherm in carbon materials.
[0027] Figure 5 The pore size distribution calculated using the density functional method by the equilibrium model of nonlocal density functional for slit-like pores is shown. The size distribution of the pores is bimodal with dominant pore sizes of 0.85 nm and 3.5 nm.
[0028] Figure 6 The imprint image of the micro-indenter is shown, demonstrating the high hardness of the carbon material.
[0029] Figure 7 The measured lateral resistance of the carbon material film is shown as the gap between the planar contacts varies. The slope of the fitted line gives a value of 0.05 S / cm for the material's conductivity.
[0030] Figure 8 The resistive behavior of carbon materials is shown for carbon materials annealed at temperatures up to 550°C.
[0031] Fig. 9 The results show that the carbon material potential is proportional to L / L + The change of the specific differential capacity of carbon materials under lithium accumulation.
[0032] Fig.10 Shown in Li + Discharge curves of carbon materials recorded under ion accumulation. Curves are taken for pure, nitrogen-doped and boron-doped carbon materials.
[0033] Fig.11 Shown are the lithium ion specific storage capacities of the carbon materials measured at C rates from 1C to 50C.
[0034] Fig.12 Shown are the discharge curves of an all-solid-state battery device based on carbon materials (nC).
[0035] Fig.13 Shown are the charge-discharge curves of a Li2S battery device using carbon material (nC). DETAILED DESCRIPTION
[0036] We organize this detailed description into the following sections, which describe non-limiting examples of the present invention:
[0037] Part 1. Fabrication of subcritical clusters
[0038] Part 2. Results of studies on subcritical cluster structures
[0039] Part 3. Results on the properties of materials containing subcritical clusters
[0040] Part 4. Summary of some characteristics of subcritical clusters and the materials they can form
[0041] Part 5: Key Features: A General Review
[0042] Part 6: Application
[0043] Part 1. Fabrication of subcritical clusters
[0044] As mentioned above, generally speaking, in the initial stages of vapor condensation, atomic clusters, each with a subcritical-sized nucleus, appear in the hot and dense vapor cloud, but are highly unstable. They rapidly appear and disappear as atoms exchange with the vapor. Our analysis of the vapor condensation literature suggests that it is believed that after the initial stage is over, the expansion and cooling of the gas vapor leads to the complete destruction of all subcritical nuclei or clusters.
[0045] Accordingly, it has previously been assumed that the growth of stable clusters, i.e., clusters of atoms, requires a supercritical core size (e.g., for carbon, greater than 1 nm), and therefore only clusters of these supercritical sizes have been analyzed. The formation of relatively large clusters, typically of the order of a few nanometers in size, is thus well understood. In contrast, subcritical-sized cores were considered so unstable that they could not be produced commercially in any manufacturing process and have therefore been largely neglected.
[0046] However, our analytical studies show that there is a special vapor condensation regime in which the growth and destruction processes can lead to the preservation of stable subcritical nuclei at some point during the vapor expansion. This leads to the formation of fairly small, stable, subcritical-sized (e.g. for carbon, subnanometer) clusters. This occurs due to a sharp increase in the characteristic times of the growth and destruction processes.
[0047] This special state requires a specific pattern of heating, ionization, and subsequent rapid expansion and cooling of the vapor cloud. In this special state, vapor condensation occurs, resulting in the formation of atomic clusters, each of which is a solidified nucleus of subcritical size - for example, a subnanometer-sized cluster of carbon atoms. We call these groups of atoms "clusters" or "subnanometer clusters". For carbon targets, this means that the size (e.g., one dimension, such as width or diameter, where clusters are usually spherical) of the clusters formed in this special process is below 1nm, because the 'critical size' of carbon is 1nm.
[0048] Our analysis shows that the possibility of implementing this special condensation state is mainly determined by the parameters of the evaporated material, as well as by the parameters of the ionized vaporized cloud, i.e., the plasma, at the very initial moments of its expansion.
[0049] The initial plasma parameters are the initial radius of its volume R0, the temperature T0 and the total number of atoms in the plasma volume N. The material parameters are: σ is the scattering cross section at the atomic collisions, T s is the temperature at which the material solidifies.
[0050] The necessary relationship between these parameters arises from the requirement to achieve a collision mode of vapor cloud expansion (a collision mode is one in which the average distance between successive atomic collisions is shorter than the characteristic length of the vapor density change):
[0051] and
[0052]
[0053] Note that the realization of the described collision mode in at least some part of the vapor cloud volume guarantees the existence of collision-free regions at the outer part of this volume where the cloud density decreases. An important result of our analysis is that clusters of subcritical size form only at the interface between the collision and collision-free regions of the expanding vapor cloud.
[0054] In the case of carbon, in one specific example, the material parameter value is: σ = 2·10 -16 cm 2 , and T s ≈3600K. Thus, the first relation is satisfied. For example, when N=10 16 cm -3 and R0 = 1 mm. These conditions can be achieved by pulsed laser under carbon vaporization. The second relationship gives the required initial plasma temperature T0 ≈ 12500 K. This condition can also be achieved by pulsed laser under carbon vaporization. The rapid expansion and rapid cooling of the vapor cloud occurs between 2 and 4 microseconds. A skilled practitioner will appreciate that many different parameter values can be selected to satisfy these two relationships.
[0055] Note that, depending on the conditions of expansion and cooling of the vapor, the clusters can transition from the subcritical state to the supercritical state due to an increase in their size, but, as outlined above, this transition can also occur without any cluster size change. The reason is that the critical size itself is not constant and in certain cases, such as a rapid drop in vapor temperature, the critical size can decrease rapidly so that the cluster size eventually becomes larger than the critical size. This is the second case of the transition to the supercritical state. Therefore, we can say that size-related cluster properties can change during the transition if this transition is accompanied by a size change. The vapor should initially be supersaturated in order to initiate the nucleation process.
[0056] It is to be noted that while the above-described fabrication process produces stable clusters of subcritical size, and it is these subcritical clusters that are particularly interesting, the process may also simultaneously produce stable clusters of supercritical size; so the carbon material may contain clusters of size less than 1 nm, but also some clusters of size greater than 1 nm. In order not to exclude materials having a certain proportion of supercritical clusters from the scope of the present invention, we further generalize to include 'nanocluster materials', defined as materials made of clusters of either completely subcritical size, or partially subcritical and partially supercritical size, or completely supercritical size.
[0057] Part 2. Results of studies on subcritical cluster structures
[0058] Using the laser evaporation process of a carbon target and the above parameters, we produced samples of carbon sub-nanoclusters. We describe our analysis results of these samples in this section. We then go on to describe the structure of these carbon sub-nanoclusters.
[0059] Figure 1.1 shows the STM image of the carbon material. The image was taken using a laboratory-modified GPI-300 tunneling microscope. t =600mV and probe current I t=10 pA. The tungsten probe used was first electrochemically sharpened and then cleaned by Ar+ milling for 4 h. During the measurement, the vacuum in the chamber was 2.4х10 -7 Ра.
[0060] Figure 1.1a Figure 1 shows an STM image of a carbon material deposited as a thin film on a highly ordered pyrolytic graphite (HOPG) substrate. The image shows that the material consists of randomly positioned spherical clusters.
[0061] Figure 1.1b shows the surface profile obtained by STM along the green line shown in Figure 1a. It can be seen that the dominant height of the film undulations is less than 1nm.
[0062] Figure 1.1c shows an STM image of a single carbon cluster of carbon material located on the HOPG smooth surface.
[0063] Figure 1.1d shows the surface profile taken by STM along the green line shown in Figure 1c. The height of the cluster is about 0.4nm, and the recorded cluster planar size is not the actual size, but is determined by the shape of the probe near its end.
[0064] Figure 2 This is an image of an amorphous carbon cluster simulated by molecular dynamics methods, density functional calculations using CASTEP and VASP codes. Ultrasoft pseudopotentials were used in this simulation. The exchange terms were evaluated using the generalized gradient approximation (GGA) and PBE functionals. Grimme's DFT-D2 method was used to account for dispersion interactions. The cluster consists of 64 carbon atoms. Although there are pentagonal and hexagonal atomic configurations on the cluster surface, some carbon atoms are located inside the cluster and the cluster structure is disordered (amorphous). This is just one possible example of a cluster; clusters can have different numbers of atoms.
[0065] Figure 3Typical Raman spectra of carbon materials are shown. Raman measurements were performed at room temperature using a T-64000 spectrometer device (produced by Horiba-Jobin Yvon, France) in a backscattering configuration. The spectrometer is equipped with a liquid nitrogen-cooled silicon CCD array, a 600 lines / mm grating and a confocal microscope, which can provide information on carbon film sections with a diameter of ~1 micron. Together with local diagnostics, we analyzed large sample areas (10×10 to 500×500μm) and subsequently mapped the Raman maps of the spectral line parameters. This procedure makes it possible to perform one of the main tasks of this study, which is to evaluate the homogeneity of structural features over the sample area. We used an excitation light wavelength of 532nm from a Nd:YAG laser (Torus, Laser Quantum, Inc.) in the measurements. The laser power on the sample was about 200mkW in a spot with a diameter of ~1μm, obtained with a 100× objective (NA=0.9). The spectrometer resolution was increased from 2.5cm –1 composition.
[0066] Figure 3 The spectral shape shown in corresponds to an amorphous carbon material.
[0067] Although these results relate to carbon, other elements such as silicon or aluminum may also be used.
[0068] In the previous section we looked at the properties of individual clusters and the properties of materials made from these clusters. We will now look at some further findings by testing the materials we made.
[0069] Part 3. Results on the properties of materials containing subcritical clusters
[0070] Figure 4 The isotherms of nitrogen adsorption-desorption in carbon sub-nano cluster materials produced using the above method are shown. BET was performed using a QuantaChrome Nova 1200e device. Before the measurement, the samples were heated to 10 -5 The sample was degassed at 150°С for 15.5 hours under a pressure of Torr. The specific surface area (S) of the sample was determined from 7 points by Brunauer-Emmett-Teller and Langmuir models in the nitrogen partial pressure range of P / P0=0.07÷0.25. The size distribution of the pores was calculated using the density functional method by analyzing the total adsorption-desorption isotherms in the nitrogen partial pressure range of 0.01÷0.99 by means of the non-local density functional equilibrium model for slit-shaped pores.
[0071] Figure 5 The pore size distribution obtained in the carbon sub-nanocluster material is presented, showing a bimodal size distribution with dominant pore sizes of 0.85 nm and 3.5 nm.
[0072] Figure 6 The imprint of a microindenter in the surface of a carbon material is shown. The carbon material is formed by tightly packed nanoclusters and has a fractal structure. That is, in the first stage, the clusters form agglomerates of small size (such as 5nm), and then these agglomerates form agglomerates of the next order of magnitude, and so on. Obviously, the higher the order of magnitude of the agglomeration, the lower the bond strength between them. Therefore, the mechanical properties of the material are highly dependent on the spatial scale. In particular, the hardness depends on the size of the indenter used. Measurements at the atomic level using the diamond probe of an atomic force microscope give values exceeding 50GPa (diamond 70-100GPa), which is the upper limit of the method. However, this method is not a standard. Microhardness measurement is a standard technique that indicates the characteristic size of the imprint, i.e. the spatial scale, in microns. Figure 6 A photograph of an imprint made under a load of 0.05 kgf on a DuraScan G50 device certified for these tests is shown. The hardness value determined from this imprint was 20 GPa. This value is equivalent to corundum (9 Mohs) and exceeds all known carbon materials except diamond.
[0073] It is worth noting that the hardness of the carbon material depends on the process conditions. The residual pressure in the chamber, the temperature and type of substrate, and doping are all important. With a certain set of parameters, the hardness can be reduced to 0.1 GPa, corresponding to a very soft material.
[0074] Figure 7 The resistance of carbon sub-nano cluster materials measured in thin films by a four-contact method at 20°C is provided. To measure the resistance, the test sample was made by depositing a thin (about 1 μm thick) carbon material film on an insulating substrate of an oxidized silicon wafer. Then, by using standard photolithography, a series of planar metal (Cr / Au) contacts were formed on the surface of the film with varying gaps between the contacts. Figure 7 The measured resistance is shown as the gap between two adjacent planar contacts varies. The slope of the fitted line gives a value of 0.05 S / cm for the material conductivity.
[0075] Figure 8 The behavior of the resistance of the carbon sub-nano cluster material when the material is annealed is shown. As shown in the figure, after annealing at 550°C, the material resistance is irreversibly reduced (conductivity increased) by three orders of magnitude.
[0076] Fig. 9 , 10Figures 1 and 11 show important data of the capacity of the carbon material (relativity of specific differential capacity to voltage, discharge capacity to material doping, and specific capacity to cycle number, respectively). The capacity of the carbon material is measured in a lithium-based energy storage device, i.e., in a battery, which comprises a thin, i.e., 100 nm thick carbon material film, a diaphragm (i.e., 25 μm thick Celgard 2325) and a lithium foil (i.e., 100 μm thick) deposited on a copper foil in sequence. The diaphragm is infiltrated with 1M LiPF6 / EC-DMC electrolyte (i.e., supplied by Tinci, China). The battery is assembled in a standard CR2032 shell. The assembly is carried out in an Ar atmosphere in a glowbox (i.e., OMNI-Lab, VacuumAtmospheres Ltd., US). Capacitance measurements and battery cycling experiments are performed in a constant current state using standard equipment (i.e., Potentiostat-Galvanostat P45X, Elins Ltd.) with a current setting accuracy of 0.2 nA and a voltage measurement accuracy of 40 μV.
[0077] Fig. 9 The specific differential capacity of the carbon materials under lithium accumulation is shown to be significantly higher, especially at voltages exceeding 1 V, which distinguishes our carbon materials from, for example, graphite, hard carbon, and different activated carbon materials.
[0078] Fig.10 The discharge curves of pure carbon material, nitrogen-doped material and boron-doped material are shown. The figure shows that nitrogen doping leads to a decrease in material capacity compared to pure carbon material, coupled with a narrowing of the voltage operation window. On the other hand, boron doping provides a significant increase in capacity, while the voltage operation window becomes wider. Therefore, the possibility of controlling the capacity and voltage operation window by material doping is demonstrated.
[0079] Fig.11 It is shown that the lithium ion specific storage capacity of our carbon material is much higher than that of other carbon materials, while the decrease in capacity of the carbon material is moderate in the C-rate variation range from 1 C to 50 C. This slow decrease in capacity at increasing C-rate is directly related to the specific property of the material, namely high ionic (Li ion) conductivity.
[0080] Fig.12 An example of an all-solid-state energy storage device is shown. The device operates based on the high mobility of Li ions in nC materials, which enables us to make an electrode (cathode in the example) consisting only of nC. To make the device, a 1 μm nC layer is deposited on a solid electrolyte (SSE) by laser evaporation. The SSE is a piece of 1 cm 2 , 1mm thick Li7La3Zr2O 12(LLZO). On the other side of the SSE, a Li foil was mechanically attached (see inset). The cell was placed into a CR2032 coin cell. The charge and discharge profiles of the device in constant current mode were measured. Fig.12 Shown in Figure 1 is the discharge curve for the 85th cycle. The test was performed at room temperature and a current of 4 μA. The device shows a specific charge capacitance of greater than 0.5 Ah / g. In this case, the solid electrolyte is just a separator between the anode and cathode that blocks the electron current and provides the ion current. Meanwhile, the carbon electrode made of nC does not contain an electrolyte.
[0081] Fig.13 A lithium-sulfur battery with a solid-state cathode is presented. It is known that lithium-sulfur batteries exhibit higher specific energy density than commercially available lithium-ion batteries. However, their use is greatly limited due to their short lifespan. The latter originates from the unfavorable interaction between reactive polysulfide species formed by elemental sulfur during operation of the lithium-sulfur battery and the carbonate-containing liquid electrolyte commonly used in rechargeable batteries. Due to this unfavorable interaction, the cathode active material of the lithium-sulfur battery, sulfur, is deactivated during battery operation, resulting in a significant reduction in the energy density of the lithium-sulfur battery. This problem can be largely solved by utilizing the unique properties of nC materials.
[0082] In this example, nC is used to provide electronic and ionic conductivity in the sulfur cathode, as well as to protect the cathode from adverse interactions of sulfur and the liquid electrolyte. The latter is based on the fact that the laser-deposited nC layer is opaque to the liquid.
[0083] A diagram of the battery assembly is shown in Fig.13 It contains an nC-based cathode, a Li foil anode, a carbonate-based liquid electrolyte (1 M LiPF6 in EC / DMC 1:1), and a separator (Celgard 2500).
[0084] The proposed cathode consists of two parts. The active part is a mixture of nC and sulfur (50:50 by mass) deposited on Al foil by standard techniques. The active area is 1.4 cm 2 The protective part is a nC layer deposited by laser evaporation above the active layer. The cell is assembled in a CR2032 coin cell.
[0085] The cells were tested in galvanostatic mode. Fig.13A typical charge-discharge curve for the 115th cycle is shown with a current of 0.25 mA (~1C). The device has been tested for 500 cycles and shows only a 15% capacitance drop. We should note that carbonates interact strongly with polysulfides formed from sulfur during cell operation. This side reaction normally makes it impossible to use carbonates in lithium-sulfur batteries. Since our device cycled for more than 500 cycles, this suggests that the protective layer is completely opaque to the liquid electrolyte. Also since the device can be charged and discharged, it can be concluded that lithium ions can effectively penetrate the protective layer and diffuse into the active layer to some extent. Taking into account the geometry of the device, the applied current and the voltage drop, we can make a minimum estimate of the ionic conductivity of nC under the given conditions, which is >10 -4 S / cm.
[0086] According to the shape of the voltage curve ( Fig.13 ), we can also note that the reaction 2Li+S<->Li2S occurs in the solid phase. Therefore, nC can be used as a universal host for solid-state batteries, providing mutual conductivity and allowing reactions to occur in the solid state.
[0087] The thermal and chemical stability of the carbon material is noteworthy. The experimental results are as follows.
[0088] 1. Heating and oxidation in air:
[0089] The carbon material is deposited on the substrate as a layer with a thickness of 30-100 microns with an area of 1-20 mm 2 The material was then heated to a temperature of 800°C and kept in air for 10 hours. After cooling, the material was weighed and its weight was 0.45 g. Thus, the weight loss was 60%. Under similar conditions, a 1.6 mm thick piece of carbon glass of the same mass was completely burned out after 5 hours.
[0090] 2. Chemical oxidation
[0091] The carbon material is ground in a planetary mill into a powder form with a characteristic particle size of about 5 μm and a maximum dimension of not more than 20 μm. The material is placed in a saturated solution of chromic anhydride (CrO3) in concentrated sulfuric acid (97% H2SO4). The mass of the carbon material is 250 mg and the volume of the oxidant is 100 ml. This provides a large excess of oxidant. The mixture of oxidant and carbon material is heated to 100°C and maintained under these conditions for 5 hours. The remaining material is then separated from the solution on a filter, washed and thoroughly dried. The residual mass of carbon material is 140 mg.
[0092] Under similar conditions, all known carbons are completely oxidized to CO2 gas. Typical oxidation times range from a few minutes (soft carbon, hard carbon, carbon nanotubes, SP, graphite) to tens of minutes (only carbon glass).
[0093] Part 4. Summary of some characteristics of subcritical clusters and the materials they can form
[0094] We will now look in more detail at some of the characteristics of subcritical size clusters and the materials they form from. We will cover the following areas:
[0095] 4A: Amorphous structure of a single subcritical cluster
[0096] 4B. High electrochemical capacity of materials formed from subcritical clusters
[0097] 4C. Deformed spherical shape of a single subcritical cluster
[0098] 4D. Subcritical cluster self-assembly
[0099] 4E. Ions can easily enter subcritical cluster materials
[0100] 4F. Configurable Shapes of Subcritical Cluster Materials
[0101] 4G. Material deposition onto substrate
[0102] 4H. Thermal and chemical stability
[0103] 4A. Amorphous structure of a single subcritical cluster
[0104] Clusters of subcritical size, such as carbon subnanoclusters, have a substantially amorphous, non-crystalline structure.
[0105] Note that "substantially" means almost all. For example, for sp 2 For hybrid carbon, it is always possible that a small fraction (e.g., 100 atoms) of the cluster has a crystalline structure. However, carbon sub-nanoclusters have essentially no internal crystalline structure or domains. Furthermore, materials composed of many of these carbon sub-nanoclusters also have essentially no crystalline domains. Molecular dynamics indicates that a single carbon sub-nanocluster can have a cluster of 64 atoms, which is structurally non-crystalline (see Figure 2 ), but clusters can be formed by different numbers of atoms; 64 is a non-limiting example.
[0106] The size of carbon sub-nanoclusters is generally less than 1 nm, and in an important implementation, the size is approximately in the range of 0.3 nm / 0.4 nm-0.7 nm. Each of these carbon clusters is essentially amorphous in structure, meaning that their atomic structure is irregular, which is typical for carbon clusters smaller than C60 fullerenes [RO Jones, Journal of Chemical Physics, 1999, 110 (11), 5189-5200] (the size of C60 is ~0.75 nm [A. Goel et al., Carbon 42 (2004) 1907–1915]).
[0107] In the carbon sub-nano cluster material, the carbon sub-nano clusters are densely and randomly stacked together. The carbon sub-nano cluster material composed of amorphous carbon sub-nano clusters is essentially amorphous. The amorphous structure of the carbon sub-nano cluster material is confirmed by the Raman spectrum obtained for the material (see Figure 3 ). Note, however, that the material produced by the above process may include not only amorphous carbon subnanoclusters, but also crystalline clusters that may be of supercritical size.
[0108] 4B. High electrochemical capacity of materials formed from subcritical clusters
[0109] Compared with hard carbon and activated carbon materials, the specific surface area of carbon sub-nano cluster materials is very moderate, about 6-8 m 2 / g, and preferably 7m 2 / g (measured by N2 physical adsorption). However, carbon sub-nano cluster materials have high ionic conductivity (e.g., 10 -4 S / cm, measured relative to Li ions). This high ionic conductivity contributes to very high levels and very high rates of ion (Li ion) accumulation in the carbon nanocluster material. We use the term "accumulation" to distinguish between "adsorption" and "intercalation"; "adsorption" and "intercalation" are not significantly relevant to this material.
[0110] Subcritical cluster materials, such as carbon subnano cluster materials, have many advantages over crystalline carbon materials such as graphite. Subcritical cluster materials have more ways to store charged ions. Graphite (~99% crystalline) can only store metal ions between graphene layers through an ion intercalation process, and this ion intercalation process is relatively slow. In contrast, amorphous subcritical cluster materials, such as carbon subnano cluster materials, can accumulate metal ions in the bulk of the material, such as on the surface of the carbon subnano clusters, and the ion accumulation proceeds at a high speed (leading to the possibility of operating at high C rates, such as Fig.11 In summary, amorphous carbon sub-nano cluster materials can accumulate more metal ions, and the ion accumulation can be carried out at a higher rate, which makes subcritical cluster materials, such as carbon sub-nano cluster materials, particularly useful in supercapacitor implementation. Fig. 9 and 11 The high electrochemical capacity of this material is shown.
[0111] 4C. Deformed spherical shape of a single subcritical cluster
[0112] Subcritical clusters, such as carbon subnanoclusters, may have a substantially spherical or deformed spherical shape and may have a diameter between 0.3 / 0.4 nm and 0.7 nm. Molecular dynamics indicates that a single carbon subnanocluster may be, for example, a cluster of 64 atoms in the shape of a deformed sphere or a deformed shell (see Figure 2 ). The shape of such small clusters is of course difficult to determine, not least because the STM measurements suggest spherical or deformed spherical shapes that are an artifact of the measurement process; however, we expect the shape of subcritical clusters not to be highly elongated but more like a deformed or crumpled shell, like a deformed sphere.
[0113] 4D. Subcritical cluster self-assembly
[0114] Clusters of subcritical size, such as carbon subnanoclusters, can self-assemble with other similar clusters to form materials in a manner that is consistent and reproducible across a large number of clusters.
[0115] The self-assembly formation of the material is beneficial for reproducibility issues. Otherwise, when making these sub-nanometer materials, it would be difficult to control the assembly of the clusters into the material in order to obtain the same material and properties every time.
[0116] 4E. Ions can easily enter subcritical cluster materials
[0117] Subcritical clusters, such as carbon subnanoclusters, self-assemble into materials with high ionic conductivity, most likely due to the very small size of the clusters in the material, allowing ions to easily enter the material.
[0118] 4F. Configurable Shapes of Subcritical Cluster Materials
[0119] Materials composed of subcritical clusters, such as carbon subnanoclusters, can be formed into desired shapes or configurations, such as thin layers or coatings or powder particles.
[0120] 4G. Material deposition onto substrate
[0121] Materials composed of subcritical clusters, such as carbon subnanoclusters, can be formed or deposited on substrates such as carbon paper, conductive (e.g., carbon and metal) wires, metal foams, and oxides. The material can be deposited on the substrate as a layer with a layer thickness ranging from about 10 nm to 500 μm, and in some cases can be separated from the substrate, and the separated material can be further ground to obtain a material powder. The material can be used for supercapacitor electrodes. We will give a more detailed example in Section 6D.5 below, in which we describe how the material can be formed onto a wire substrate.
[0122] 4H. Thermal and chemical stability
[0123] Materials composed of subcritical clusters, such as carbon subnanoclusters, exhibit excellent thermal and chemical stability. These features contribute to the long cycle life of energy storage devices, such as Fig.11 as shown in .
[0124] Part 5: Key Features: A General Review
[0125] In this section, we bring together a comprehensive summary of all key features in one place. It is organized as follows:
[0126] 5A. Fabrication of subcritical clusters
[0127] 5B. Summary of characteristics of subcritical size clusters
[0128] 5C. Summary of Characteristics of Carbon Subnanoclusters
[0129] 5D. Summary of the characteristics of materials containing multiple subcritical size clusters
[0130] 5E. Summary of the characteristics of materials containing multiple carbon sub-nanoclusters
[0131] 5F. Summary of the unique properties of materials containing multiple carbon sub-nanoclusters
[0132] 5G. These feature sets extend to nanoclusters
[0133] Note that each feature set can be combined with any other feature set; optional features can be combined with any feature set.
[0134] 5A. Fabrication of subcritical clusters
[0135] We can summarize the manufacturing process in the following set of characteristics1:
[0136] Feature Set 1: Making Subcritical Clusters
[0137] A method of making stable atomic clusters of subcritical size, wherein a vapor cloud undergoes rapid expansion and rapid cooling, wherein vapor conditions or parameters are controlled such that a plurality of stable clusters are condensed, each of which has a size less than a critical size, or are formed in a subcritical nucleation process.
[0138] A method of making stable atomic clusters, wherein a vapor cloud undergoes rapid expansion and rapid cooling, wherein vapor conditions or parameters are controlled such that a plurality of stable clusters, each formed in a subcritical nucleation process that would otherwise result in its destruction, are condensed into a stable cluster.
[0139] A method of producing stable atomic clusters of subcritical size, wherein the expansion of a vapor cloud is controlled to a state where the destruction of clusters of subcritical size or formed during subcritical nucleation is substantially complete or reduced.
[0140] A method of producing stable atomic clusters of subcritical size or formed in a subcritical nucleation process by directly or indirectly controlling one or more parameters that vary with the material and the vaporization and condensation conditions.
[0141] A method of making stable subcritical clusters using laser evaporation, wherein a vapor cloud undergoes rapid expansion and rapid cooling, wherein vapor conditions or parameters are controlled such that a plurality of stable clusters are condensed, each of which has a size less than a critical size or is formed during a subcritical nucleation process.
[0142] • In each of the above cases, when the clusters are made of carbon, the size of the clusters is less than 1 nm, for example between 0.3 / 0.4 nm and 0.7 nm. We can also define the method of generating subcritical clusters in more detail, as follows.
[0143] A method for producing stable subcritical atomic clusters, wherein a vapor cloud undergoes rapid expansion and rapid cooling, and vapor generation conditions at the time of initial vapor expansion are set or controlled so that stable atomic clusters are condensed, each of which has a size less than a critical size or is formed in a subcritical nucleation process.
[0144] A method of making stable subcritical atomic clusters in which a vapor cloud undergoes rapid expansion and rapid cooling, and the vapor generation conditions at the time of initial vapor expansion are arranged or controlled to provide that the vapor expansion (i) does not occur so rapidly that clusters of any size do not have sufficient time to form, and (ii) does not occur so slowly that any subcritical size clusters disappear by exchange with vapor phase atoms.
[0145] A method of producing a stable subcritical atomic cluster, wherein a vapor cloud undergoes rapid expansion and rapid cooling and the vapor generation conditions are set or controlled to provide a vapor cloud expansion in a collision mode, wherein the collision mode means that the average distance between successive atomic collisions is shorter than the characteristic length of the vapor density change):
[0146] and
[0147]
[0148] The initial plasma parameters are the initial radius of its volume R0, the temperature T0 and the total number of atoms in the plasma volume N. The material parameters are: σ is the scattering cross section at the atomic collisions, T s is the temperature at which the material solidifies.
[0149] o Clusters of subcritical size form at the interface between those volumes of the expanding vapor cloud that are in collision mode and regions outside of these collision mode volumes that are not (or at least substantially not) in collision mode.
[0150] o When the expanding vapor cloud volume is in collision mode, then it results in the presence of a collisionless (i.e., substantially collisionless mode) zone outside the expanding vapor cloud volume, wherein the cloud density decreases, and clusters of subcritical size form at the interface or boundary between the collision mode volume and the collisionless zone of the expanding vapor cloud.
[0151] o For carbon, in one non-limiting example, the material parameter value is substantially equivalent to: σ = 210 -16 cm 2 , T s ≈3600K. Thus, the first relation is satisfied. For example, when N=10 16 cm -3 and R0 = 1 mm. The second relation gives the required initial plasma temperature T0 ≈ 12500 K.
[0152] The subcritical clusters can be produced using established techniques:
[0153] The pulsed laser evaporation process of the carbon target is configured to meet or provide the conditions or parameters defined above.
[0154] An industrially scalable process in which a high density plasma of ions is produced using a source of highly intense excited atoms and the process is configured to meet or provide the conditions or parameters defined above.
[0155] We can also generalize the process used to generate subcritical clusters:
[0156] A process for making subcritical sized clusters of atoms in which a source of high intensity excitation of these atoms causes a plasma vapor cloud of these atoms to expand rapidly; and in which vapor conditions are controlled so that, at least in certain portions or volumes of the vapor cloud, the vapor cloud is in a collision mode, and stable clusters of subcritical size are formed at the interface between those volumes of the expanding vapor cloud that are in collision mode and regions outside of these collision mode volumes that are not in (or at least substantially not in) collision mode.
[0157] A method for producing stable subcritical clusters using laser evaporation of a fast flowing jet of carbon-containing gas, wherein the laser evaporation results in extensive gas heating and gas decomposition, followed by rapid expansion and rapid cooling of the carbon vapor cloud with controlled vapor cooling and expansion conditions, so that a plurality of stable clusters are condensed, each of which has a size less than a critical size.
[0158] A method of making stable subcritical clusters utilizing rapid compression and ionization of a carbon-containing gas by rapid reconnection of magnetic field lines and subsequent gas decomposition, rapid expansion and rapid cooling of a carbon vapor cloud with controlled vapor cooling and expansion conditions such that a plurality of stable clusters are condensed, each of said clusters having a size less than a critical size.
[0159] Optional Features:
[0160] o The laser evaporation process produces a high intensity excitation of the source.
[0161] o A laser beam is directed toward a carbon-containing substance (e.g., a bulk carbon target or a carbon-containing gas), and then a high-density carbon ion plasma is generated, in which carbon vapor condenses, resulting in the formation of stable carbon subcritical clusters, such as subnanometer clusters.
[0162] оThe process uses continuous wave or pulsed laser evaporation
[0163] oThe process uses a laser-on-gas process and magnetic control of the plasma
[0164] o Stable subcritical clusters are defined in Feature Set 2 below.
[0165] o Stable subcritical clusters are stable subnano carbon clusters as defined in Feature Set 3 below or nanoclusters as defined in Feature Set 7 below.
[0166] Note that any of the methods defined above can be used to make materials formed from stable subcritical clusters, and the materials can be further defined below in Feature Set 4, Feature Set 5, and Feature Set 6. Thus, the formed material can include both stable subcritical clusters and stable supercritical clusters.
[0167] 5B. Summary of characteristics of subcritical size clusters
[0168] We summarize our description of subcritical size clusters in Feature Set 2 below:
[0169] Feature Set 2: Defining Subcritical Clusters
[0170] A stable cluster of atoms of a specific element, the size of which is smaller than the critical size of the specific element.
[0171] Stable clusters of atoms of a particular element, formed in a subcritical nucleation process that is controlled to preserve subcritical nuclei that would otherwise be destroyed.
[0172] Stable clusters of atoms of a particular element, the cluster size being less than the critical size for the particular element or being formed in a subcritical nucleation process that is controlled so as to preserve subcritical nuclei that would otherwise be destroyed, and wherein the clusters have a significantly distorted spherical shape.
[0173] Stable clusters of atoms of a particular element having a size less than a critical size for the particular element or formed in a subcritical nucleation process that is controlled to preserve subcritical nuclei that would otherwise be destroyed, and wherein the clusters have a substantially amorphous, non-crystalline structure.
[0174] - A stable cluster of atoms as defined above, wherein the atoms are carbon.
[0175] • A stable cluster of atoms as defined above, wherein the atoms are carbon and in one example are formed into an amorphous 64 carbon structure.
[0176] - A stable cluster of atoms as defined above, wherein the atoms are silicon.
[0177] A stable atomic cluster of a specific element, having a size smaller than the critical size of the specific element, produced using the method defined in Feature Set 1 above.
[0178] 5C. Summary of Characteristics of Carbon Subnanoclusters
[0179] We summarize the description for the special case where the atoms in the cluster are carbon (so we have carbon subnanoclusters) in feature set 3 below:
[0180] Feature Set 3: Defining Carbon Subnanoclusters
[0181] A stable carbon sub-nano cluster with a size less than 1 nm.
[0182] A stable carbon sub-nano cluster with a size between 0.3 / 0.4nm and 0.7nm.
[0183] A stable carbon sub-nano cluster formed in a subcritical nucleation process that is controlled to preserve subcritical nuclei that would otherwise be destroyed.
[0184] A stable carbon sub-nano cluster having a size of less than 1 nm, and wherein the sub-nano cluster has a substantially spherical or distorted spherical shape.
[0185] A stable carbon sub-nano cluster with a size less than 1 nm and a substantially amorphous, non-crystalline structure.
[0186] A stable sub-nano cluster as defined above, wherein the atoms are carbon and as an example are formed into an amorphous 64 carbon structure.
[0187] A stable carbon sub-nano cluster produced using the method defined in Feature Set 1 above.
[0188] A stable carbon sub-nano cluster having the characteristics defined in characteristic set 2 above.
[0189] 5D. Summary of the characteristics of materials containing multiple subcritical size clusters
[0190] We summarize our description of materials containing multiple subcritical size clusters in Feature Set 4 below:
[0191] Feature Set 4: Defining a material containing multiple subcritical size clusters
[0192] • A material comprising a plurality of stable atomic clusters of a particular element, wherein at least some of the clusters each have a size smaller than the critical size of the particular element.
[0193] • A material comprising a plurality of stable atomic clusters of a particular element, wherein at least some of the clusters are formed in a subcritical nucleation process that is controlled so as to preserve subcritical nuclei that would otherwise be destroyed.
[0194] • A material comprising a plurality of stable atomic clusters of a particular element, wherein at least some of the clusters have a size smaller than a critical size of the particular element and wherein each of the clusters has a substantially amorphous, non-crystalline structure.
[0195] A material comprising a plurality of stable atomic clusters of a specific element, wherein at least some of the clusters have a size smaller than a critical size of the specific element and each of the clusters has a substantially amorphous, non-crystalline structure, and the material also has a substantially amorphous, non-crystalline structure.
[0196] • A material comprising a plurality of stable atomic clusters of a particular element, wherein at least some of the clusters have a size smaller than the critical size of the particular element and also have a substantially spherical or distorted spherical shape.
[0197] - A material comprising a plurality of stable atomic clusters of a specific element, wherein at least some of the clusters have a size smaller than the critical size of the specific element and wherein the clusters self-assemble to fully or partially form the material.
[0198] A material comprising a plurality of stable atomic clusters of a particular element, wherein at least some of the clusters have a size less than a critical size of the particular element and wherein the clusters consistently and reproducibly self-assemble in the same manner to fully or partially form the material.
[0199] A material comprising a plurality of stable atomic clusters of a specific element, wherein each cluster has a size smaller than the critical size of the specific element and is produced using the method defined in Feature Set 1 above.
[0200] A material as defined in this feature set 4, produced using the method defined in the above feature set 1.
[0201] - A material as defined above, wherein the atoms are carbon atoms.
[0202] - A material as defined above, wherein the atoms are silicon atoms.
[0203] 5E. Summary of the characteristics of materials containing multiple carbon sub-nanoclusters
[0204] And for the specific case where the atoms in the cluster are carbon (so we have a material containing carbon subnanoclusters), we summarize our description of materials containing multiple subcritical size clusters in Feature Set 5 below:
[0205] Feature Set 5: Defining a material containing multiple carbon sub-nanoclusters
[0206] A material containing multiple stable carbon sub-nanoclusters, each with a size of less than 1 nm.
[0207] • A material comprising a plurality of stable carbon subnanoclusters, each cluster formed in a subcritical nucleation process that is controlled to preserve subcritical nuclei that would otherwise be destroyed.
[0208] • A material comprising a plurality of stable carbon sub-nanoclusters, the size of the clusters being between 0.3 / 0.4 nm and 0.7 nm.
[0209] • A material comprising a plurality of stable carbon sub-nanoclusters, and wherein at least some of the carbon sub-nanoclusters have a substantially amorphous, non-crystalline structure.
[0210] • A material comprising a plurality of stable carbon sub-nanoclusters, and wherein at least some of the carbon sub-nanoclusters have a substantially amorphous, non-crystalline structure, and wherein the material also has a substantially amorphous, non-crystalline structure.
[0211] • A material comprising a plurality of stable carbon sub-nanoclusters, and wherein at least some of the carbon sub-nanoclusters have a substantially spherical or distorted spherical shape.
[0212] - A material comprising carbon sub-nanoclusters, each cluster having a substantially amorphous, non-crystalline structure, wherein the sub-nanoclusters self-assemble to fully or partially form the material.
[0213] A material comprising carbon sub-nanoclusters, wherein the pores between the carbon sub-nanoclusters are sized to allow ions of a selected element to move freely or substantially easily into and out of the pores.
[0214] A material comprising carbon sub-nanoclusters, wherein the pore size between the carbon sub-nanoclusters is set to allow ions of selected elements to move in and out freely or substantially easily, and the accumulation of metal ions is at least 60-150 pm.
[0215] A material comprising carbon sub-nanoclusters, wherein the material has a 6-8 m 2 / g, and has a very moderate specific surface area, such as 10 -4 S / cm, which contributes to very high levels and high rates of ion accumulation in the carbon sub-nanocluster materials.
[0216] A material comprising carbon sub-nanoclusters, wherein the material has a 6-8 m 2 / g, and preferably 7m 2 / g (measured by N2 physical adsorption) with a very moderate specific surface area and high ionic conductivity, for example 10 -4 S / cm, which contributes to the very high level and high speed of ion (Li ion) accumulation in the carbon sub-nanocluster material.
[0217] A material comprising carbon sub-nanoclusters, each cluster having a substantially amorphous non-crystalline structure, wherein the clusters accumulate metal ions in the bulk of the material, i.e., on the surface of the carbon sub-nanoclusters, thereby allowing high ion accumulation to provide high electrochemical capacity.
[0218] - A material comprising carbon sub-nanoclusters, wherein the material is formed into a desired shape or configuration.
[0219] A material comprising carbon sub-nanoclusters, wherein the material is formed or deposited on a substrate such as carbon paper, conductive (e.g. carbon and metal) wires, metal foams and oxides. The material can then be deposited on the substrate as a layer with a layer thickness ranging from about 10 nm to 500 μm; in some cases it can be separated from the substrate, and the separated material can be further ground to obtain a material powder; this can be used for supercapacitor electrodes.
[0220] A material as defined in this feature set 5, produced using the method defined in feature set 1 above.
[0221] 5F. Summary of the unique properties of materials containing multiple carbon sub-nanoclusters
[0222] We have seen above that carbon subnanoclusters have some unusual properties. We summarize and expand on these unusual properties in Feature Set 6 below:
[0223] Feature Set 6: Peculiar Properties of Materials Containing Multiple Carbon Subnanoclusters
[0224] A carbon material having a specific surface area of 6.6-8.7 m 2 / g, and the pore size distribution is bimodal with the dominant pore size between 0.85nm and 3.5nm.
[0225] A carbon material having a hardness of 0.1 GPa to 30 GPa.
[0226] A carbon material whose hardness can be varied from about 0.1 GPa to about 20 GPa by varying the conditions or parameters of the manufacturing process defined in feature set 1.
[0227] A carbon material whose hardness can be varied from about 0.1 GPa to 20 GPa by varying one or more of the following parameters: residual pressure, temperature, substrate type, doping.
[0228] A carbon material having a hardness of at least about 20 GPa.
[0229] A carbon material with a hardness of less than 1 GPa.
[0230] A carbon material with a hardness of about 0.1 GPa.
[0231] A carbon material that is more resistant to oxidation when heated in air than glassy carbon.
[0232] A carbon material that resists oxidation in air up to a temperature of 1500°C.
[0233] A carbon material that is more resistant to chemical oxidation than glassy carbon.
[0234] - A carbon material having an electronic conductivity in the range of 0.01 to 0.1 S / cm at 20°C, wherein the electronic conductivity increases, for example, irreversibly increases by three orders of magnitude when the material is annealed at 550°C.
[0235] A carbon material having a -4 Li ion conductivity in S / cm
[0236] A carbon material having a relative + At a voltage exceeding 1.0 V, and when the carbon material is incorporated into an electrode of a lithium-based energy storage device, for example, it has a lithium storage specific differential capacity greater than 500 F / g.
[0237] A carbon material having a relative + At a voltage exceeding 1.0 V, and when the carbon material is incorporated into an electrode of a lithium-based energy storage device, for example, it has a lithium storage specific differential capacity greater than 1000 F / g.
[0238] A carbon material having a relative + At a voltage exceeding 1.0 V, and when the carbon material is incorporated into an electrode of a lithium-based energy storage device, for example, it has a lithium storage specific differential capacity greater than 2000 F / g.
[0239] A carbon material modified by doping with an element having a different valence from carbon to provide variable properties of the carbon material, such as by L + The ions control the capacity and operating voltage window when charging and discharging the material.
[0240] A carbon material whose Li-ion specific storage capacity does not decrease significantly with increasing C-rate, so that C-rate is not a limiting factor in selecting the material for use in lithium-based energy storage devices.
[0241] A carbon material that, when incorporated into an electrode of a lithium-based energy storage device, has a Li-ion specific storage capacity that decreases from its intrinsic value (measured at 0.1C rate) by 8% at 1C rate, by 16% at 5C rate, by 20% at 10C rate, by 28% at 20C rate, and by 36% at 50C rate.
[0242] A carbon material having a Li-ion specific storage capacity that decreases by less than 10% at 1C rate (from its intrinsic value at 0.1C rate) and by less than 20% at 5C rate.
[0243] - A carbon material whose Li-ion specific storage capacity decreases by less than 20% at a 5C rate (from its intrinsic value at a 0.1C rate).
[0244] - A carbon material whose Li-ion specific storage capacity decreases by less than 30% at a 10C rate (from its intrinsic value at a 0.1C rate).
[0245] - A carbon material whose Li-ion specific storage capacity decreases by less than 40% at a 2OC rate (from its intrinsic value at a 0.1C rate).
[0246] - A carbon material whose Li-ion specific storage capacity decreases by less than 50% at a 50C rate (from its intrinsic value at a 0.1C rate).
[0247] · The carbon material defined in this feature set 6, wherein the carbon material itself is further defined in the above feature set 4 or 5.
[0248] · A carbon material as defined in this feature set 6, produced using the method defined in the above feature set 1.
[0249] · The carbon material as defined in this feature set 6, wherein the carbon material comprises stable subcritical clusters as defined in feature set 2, or stable subnanometer carbon clusters as defined in feature set 3, or nanoclusters as defined in feature set 7.
[0250] 5G. These feature sets extend to nanoclusters
[0251] Feature Set 7: These feature sets are extended to nanoclusters
[0252] While the above feature set focuses on subcritical and subnanoclusters, we can generalize to 'nanoclusters' (i.e. clusters that can be completely subcritical, or partially subcritical and partially supercritical, or completely supercritical). We can also generalize to 'nanocluster materials' (i.e. materials made of clusters that can each be completely subcritical, or partially subcritical and partially supercritical, or completely supercritical).
[0253] The method of feature set 1, wherein the method steps are used to produce stable subcritical clusters, and stable nanoclusters.
[0254] The method of feature set 1, wherein the method steps are used to produce stable nanoclusters, as well as unstable subcritical clusters.
[0255] Nanoclusters may have some or all of the characteristics of subcritical clusters; we summarize them as follows:
[0256] A stable nano-atom cluster, wherein the nano-cluster has a substantially spherical or distorted spherical shape.
[0257] A stable nano-scale atomic cluster, wherein the nano-cluster has a substantially amorphous, non-crystalline structure.
[0258] Nanocluster materials may have some or all of the characteristics of subcritical materials; we summarize them as follows:
[0259] A material comprising a plurality of stable nano-atomic clusters, each of which has a substantially amorphous, non-crystalline structure.
[0260] A material comprising a plurality of stable nano-atomic clusters, each of which has a substantially amorphous, non-crystalline structure, and the material also has a substantially amorphous, non-crystalline structure.
[0261] • A material comprising a plurality of stable nanoscale atomic clusters, wherein the nanoclusters self-assemble to fully or partially form the material.
[0262] A material comprising a plurality of stable nanoscale atomic clusters, and wherein the nanoclusters self-assemble consistently and reproducibly in the same manner to fully or partially form the material.
[0263] Part 6: Application
[0264] While the applications of subcritical size clusters and materials containing these clusters can be argued to be as broad and deep as those of nanotechnology, some of the most important applications are stated in this section.
[0265] 6A. Energy storage device
[0266] An energy storage device comprising a plurality of stable subcritical size atomic clusters. The clusters are further defined in Section 5B (Feature Set 2) above.
[0267] An energy storage device comprising a plurality of stable sub-nanometer carbon atom clusters. The clusters are further defined in Section 5C (Feature Set 3) above.
[0268] • An energy storage device comprising a material comprising a plurality of subcritical size clusters as defined in Section 5D (Feature Set 4) above.
[0269] • An energy storage device comprising a material comprising a plurality of carbon sub-nanoclusters as defined in Section 5E (Feature Set 5) or Section 5F (Feature Set 6) above or a nanocluster as defined in Section 5G (Feature Set 7) above.
[0270] • An energy storage device comprising a material comprising a plurality of silicon subcritical clusters as defined in Section 5E (Feature Set 5) above.
[0271] ·As described in Section 3 above, the cluster or material can: form on or form part of an electrode; form on or form part of an electrode that is part of a solid-state battery; act as an ion host or matrix; act as an ion host or matrix in a solid-state battery and allow solid-state phase reactions to occur at the electrode; form on or form part of an electrode to prevent electrolyte from entering the electrode; act as a protective layer to prevent undesirable interactions between the electrode material and the liquid electrolyte; form on or form part of an electrode to provide ionic and electronic conductivity while providing a protective layer to prevent liquid electrolyte from reaching the portion of the electrode covered by the cluster or material; provide sustained high specific capacity as well as high ionic conductivity and high electronic conductivity.
[0272] A car, van, truck, motorcycle, electric scooter, bicycle, aircraft, drone, satellite, smart phone, smart watch, mobile phone, tablet computer, laptop computer, electronic device, or any other type of vehicle or device that includes an energy storage device as defined in this section 6A.
[0273] 6B. Grinding powder
[0274] - A milled powder comprising a plurality of stable subcritical size atomic clusters. The clusters are further defined in Section 5B (Feature Set 2) above.
[0275] A milled powder comprising a plurality of stable sub-nanometer carbon atom clusters. The clusters are further defined in Section 5C (Feature Set 3) above.
[0276] • A milled powder comprising a material comprising a plurality of subcritical size clusters as defined above in Section 5D (Feature Set 4).
[0277] • A milled powder comprising a material comprising a plurality of carbon subnanoclusters as defined above in Section 5E (Feature Set 5) or Section 5F (Feature Set 6) or nanoclusters as defined in Section 5G (Feature Set 7).
[0278] 6C. Supercapacitor type energy storage device
[0279] A supercapacitor comprising a plurality of stable subcritical size atomic clusters. The clusters are further defined in Section 5B (Feature Set 2) above.
[0280] A supercapacitor comprising a plurality of stable sub-nanometer carbon atom clusters, the clusters being further defined in Section 5C (Feature Set 3) above.
[0281] • A supercapacitor comprising a material comprising a plurality of subcritical size clusters as defined in Section 5D (Feature Set 4) above.
[0282] • A supercapacitor comprising a material comprising a plurality of carbon subnanoclusters as defined in Section 5E (Feature Set 5) or Section 5F (Feature Set 6) above or a nanocluster as defined in Section 5G (Feature Set 7).
[0283] • The clusters or materials may be formed on or form part of a supercapacitor electrode.
[0284] A car, van, truck, motorcycle, electric scooter, bicycle, aircraft, drone, satellite, smart phone, smart watch, mobile phone, tablet, laptop, computer, electronic device, or any other type of vehicle or device that includes an ultracapacitor as defined in this section 6C or section 6D below.
[0285] We will now expand on some specific characteristics of supercapacitors and batteries.
[0286] 6D.1 Lithium-ion supercapacitor
[0287] The supercapacitor defined in section 6C above may be a lithium ion supercapacitor in which the Li ions are accumulated in a material as defined in section 5D or 5E or 5F above. There is no intercalation; accumulation is the key mechanism.
[0288] • The electrode is not activated carbon, but is a material comprising a plurality of carbon sub-nanoclusters as defined above in Section 5E (Characteristic Set 5) or Section 5F (Characteristic Set 6).
[0289] The charge and discharge rate exceeds 100C and can reach or exceed 200C, or even higher, such as 600C
[0290] No or very limited performance degradation after 5,000 or even 10,000 charge / discharge cycles
[0291] Lithium metal is one terminal, the carbon material is the other terminal; and the electrolyte is in the group of: lithium sulfide or lithium oxide or lithium phosphate; (Li3PS4 (sulfide) and Li 1.3 Al 0.3 Ti 1.7 (PO4)3 (phosphate) and Li7La3Zr2O 12 (oxide); or lithium polymer, or lithium argyrodite or phosphorus sulfide.
[0292] 6D.2 Magnesium Supercapacitor
[0293] The supercapacitor defined in section 6C above may be a magnesium ion supercapacitor, wherein the Mg ions are accumulated in a material as defined in section 5D or 5E or 5F above. There is no intercalation; accumulation is the key mechanism.
[0294] Magnesium can be one terminal, a material as defined in Section 5D or Section 5E or Section 5F above is the other terminal, and the electrolyte is magnesium scandium selenide MgSc2Se4 or a polymer.
[0295] • Magnesium may be one terminal, a material as defined in Section 5D or Section 5E or Section 5F above is the other terminal, and is covered by a liquid electrolyte.
[0296] 6D.3 Aluminum Supercapacitor
[0297] The supercapacitor defined in Section 6C above may be an aluminum ion supercapacitor, wherein Al, or a composite containing aluminum ions such as AlCl4 - , accumulated in a material as defined in Section 5D or Section 5E or Section 5F above.
[0298] Aluminum can be one terminal, the carbon sub-nano cluster system is another terminal; and the electrolyte is aluminum sulfide or aluminum oxide Al2O3, or manganese dioxide MnO2
[0299] Aluminum may be one terminal, a material as defined in Section 5D or Section 5E or Section 5F above is the other terminal, and is covered by a liquid electrolyte.
[0300] 6D.4 Solid electrolytes and solid batteries
[0301] A supercapacitor as defined in section 6C may comprise a material as defined in section 5D or section 5E or section 5F above, said material being covered by a solid electrolyte.
[0302] As described in Section 3 above, the carbon nanocluster material has both electronic conductivity and high ionic conductivity and can be successfully used to design efficient all-solid-state batteries. In one implementation of such a battery, a carbon nanocluster material layer can be deposited on a current collector to form a first battery electrode. Thereafter, a solid electrolyte material layer with extremely low electronic conductivity is deposited on the carbon nanocluster material layer (e.g., using laser enhanced deposition or pulsed laser deposition). Finally, an opposing (second) battery electrode (anode or cathode) is formed. In the resulting element, the solid electrolyte material layer provides electrical isolation of the two battery electrodes. Recalling Section 3, a lithium-ion solid-state battery includes (a) a cathode made of a carbon nanocluster material; (b) a solid electrode, such as Li7La3Zr2O 12 (LLZO); (c) lithium foil anode.
[0303] The advantages of such batteries stem from the unique characteristics of carbon nanocluster materials, namely, sustained high specific capacity as well as high ionic and electronic conductivity.
[0304] In another implementation of an all-solid-state battery, the carbon nanocluster material can be deposited simultaneously with a solid electrolyte material to form a composite electrode layer. In this case, the solid electrolyte can form a self-assembled network around the carbon sub-nanoclusters, thereby illustrating the migration of ions to all or substantially all of the surface area of the carbon. A solid electrolyte layer is then deposited on the composite electrode layer, and then a second electrode is formed. Another advantage of this battery design can be improved ionic and electronic contact between the composite electrode layer and the solid electrolyte layer.
[0305] In another implementation of an all-solid-state battery, the carbon nanocluster material can be deposited simultaneously with sulfur to form a composite cathode electrode layer. A solid electrolyte layer is then deposited. Finally, an anode electrode layer is formed. One advantage of this battery design over similar battery designs with only carbon nanocluster material in the cathode layer is that the operating voltage is increased, thereby increasing the specific storage energy. This advantage is particularly provided by adding sulfur to the cathode electrode layer. Recalling Section 3, a lithium-sulfur battery includes (a) a solid cathode made of carbon nanocluster material, mixed with sulfur and deposited on aluminum foil, and covered with a protective layer of carbon nanocluster material that is impermeable to liquid electrolyte; (b) a carbonate-based liquid electrolyte; (c) a separator; and (d) a lithium foil anode.
[0306] We note that the special properties of carbon nanocluster materials, which combine high specific capacity, high ionic conductivity and high electronic conductivity, can be used in a variety of ways, not limited to the above-mentioned implementation examples, to improve the characteristics of batteries, including batteries with solid and liquid electrolytes.
[0307] 6D.5 Linear substrates of sub-nanometer cluster materials
[0308] The material as defined in Section 5D or Section 5E or Section 5F above may be formed on a substrate of conductive wires or fibers or other linear or elongated conductive structures. In this form, it may be used in batteries or supercapacitors or other forms of energy storage devices.
[0309] The substrate is any conductive material
[0310] The substrate is any conductive microporous material
[0311] ·The wire is a metal wire
[0312] Fiber is conductive carbon fiber
[0313] The fibers are conductive metal oxide fibers.
[0314] · Wires or fibers or other elongated structures covered with carbon sub-nano clusters
[0315] The substrate is a pair of wires, fibers or other elongated conductive structures, each of which is covered with a solid electrolyte before the pair of substrates are assembled.
[0316] • A solid electrolyte fills the gap between the pair of wires, fibers or other elongated conductive structures.
[0317] The pair of wires, fibers or other elongated conductive structures are twisted together.
[0318] The solid electrolyte comprises carbon sub-nanoclusters that have formed into a self-assembled monolayer or multiple self-assembled monolayers.
[0319] The substrate is made of one or more of the following: aluminum, copper, nickel, carbon, porous carbon.
[0320] Carbon sub-nano clusters form a self-assembled monolayer or multiple self-assembled monolayers on a wire or fiber or other elongated structure
[0321] Note that the substrate can be any porous conductive substrate on which we can coat our sub-nanometer clusters. Notable options are 3D structures consisting of or containing porous aluminum, copper, nickel, carbon, etc., encapsulating sub-nanometer carbon clusters.
Claims
1. A method of producing stable atomic clusters of subcritical size, wherein a vapor cloud is expanded and cooled, wherein vapor conditions or parameters are controlled such that a plurality of subcritical stable clusters are formed during a subcritical nucleation process during condensation of the vapor cloud; wherein the expansion and cooling of the vapor cloud occurs between 1 and 10 microseconds; The vapor cloud is composed of carbon atoms, and stable subcritical carbon clusters are generated during the condensation of the vapor cloud. The size of the stable subcritical carbon clusters is less than 1 nanometer.
2. The method of claim 1, wherein the expansion of the vapor cloud is controlled to a state where the destruction of clusters having a subcritical size is substantially complete or reduced.
3. The method of claim 1, wherein expansion and cooling of the vapor cloud occurs, and vapor generation conditions at the time of initial vapor expansion are set or controlled so that stable atomic clusters are compressed, each of which has a subcritical size.
4. The method of claim 1 , wherein expansion and cooling of the vapor cloud occurs, and vapor generation conditions at the time of initial vapor expansion are arranged or controlled to provide that the vapor expansion (i) does not occur so rapidly that clusters of any size do not have sufficient time to form, and (ii) does not occur so slowly that any subcritical size clusters disappear by exchange with vapor phase atoms.
5. The method of claim 1, wherein the expansion and cooling of the vapor cloud occurs between 2 and 4 microseconds.
6. The method of claim 1 wherein subcritical size clusters are formed at the interface between those volumes of the expanding vapor cloud that are in collision mode and regions outside of those collision mode volumes that are not in collision mode.
7. The method according to claim 1, wherein: When the expanding vapor cloud volume is in collision mode, it results in the presence of a collision-free zone outside the expanding vapor cloud volume, where the cloud density decreases and subcritical size clusters are formed at the interface or boundary between the collision mode volume and the collision-free zone of the expanding vapor cloud.
8. The method of claim 1, wherein the vapor cloud is expanded and cooled, and the vapor generation conditions are arranged or controlled to provide the vapor cloud expansion in a collision mode, wherein the collision mode means that the average distance between successive atomic collisions is shorter than a characteristic length of vapor density variation: and . The initial plasma parameters are the initial radius R0 of its volume, the temperature T0 and the total number of atoms N in the plasma volume; and the material parameters are: σ is the scattering cross section at the atomic collision, T s is the solidification temperature of the material.
9. The method of claim 1, wherein an industrially scalable process is used to generate a plasma of ions by exciting an atomic source, and the process is configured to meet or provide the conditions or parameters as defined in claim 1.
10. A method according to claim 1, wherein a source of high intensity excitation of these atoms causes a plasma vapor cloud of these atoms to expand; and wherein the vapor conditions are controlled so that at least in certain portions or volumes of the vapor cloud, the vapor cloud is in a collision mode, and stable clusters of subcritical size are formed at the interface between those expanding vapor cloud volumes in collision mode and regions outside these collision mode volumes that are not in collision mode.
11. The method of claim 9, wherein a laser evaporation process produces the excitation of the source of atoms.
12. The method according to claim 1, wherein a laser beam is directed to a carbon-containing substance and then a high-density carbon ion plasma is generated in which carbon vapor condensation occurs, resulting in the formation of stable carbon subcritical clusters.
13. The method according to claim 12, wherein the carbon-containing substance is a bulk carbon target or a carbon-containing gas.
14. The method according to claim 1 utilizes compression and ionization of carbon-containing gas, controls vapor cooling and expansion conditions to expand and cool the carbon vapor cloud by reconnecting magnetic field lines and subsequent gas decomposition, so that a plurality of stable clusters are condensed, each of which has a subcritical size.
Citation Information
Patent Citations
Device for vapor deposition of thin film
JP1985113418A
Thin film forming device
JP1991158460A